Tingkat pengetahuan dan sikap ibu berkaitan dengan ketepatan pemberian MP-ASI bayi usia 6-12 bulan di Kelurahan Lubang Buaya, Jakarta - Srimiati, Mia; Melinda, Friska (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
The golden period is a critical period in infants, and this period occurs at the age of 0-24 because it is a period of rapid growth and development. WHO/UNICEF recommends four important things, including complementary food for the infant. The important problems in the provision of complementary should be accurate in time, frequency, portion, type of food, and how to give the food at the early stage. The study aimed to analyze the relationship between the level of knowledge and attitudes of mothers about complementary feeding with the accuracy of giving complementary food of infants aged 6-12 months. This research method uses a cross-sectional research design with a quantitative research type, presented in a descriptive-analytic way, and has a sample of 60 people. Data collected by the interview method were: the characteristics of the mother, the mother's knowledge, mother's attitude, and the accuracy of giving complementary feeding, then analyzed with Chi-Square. The results was Â indicated that mothers who had moderate knowledge about complementary feeding as much as 80%, a negative attitude towards giving complementary feeding as much as 51,7%, and inappropriate in giving complementary food as much as 56,7%. There was a significant relationship between the level of mother's knowledge (p= 0,000) and mother's attitude (p= 0,000) regarding a complementary feeding and the accuracy of giving it. Concluded, knowledge and attitudes of mothers about complementary feeding has a correlation with the accuracy of giving complementary feeding for infants aged 6-12 months in Lubang Buaya, East Jakarta.Â Periode emas merupakan masa kritis pada bayi, periode tersebut terjadi pada usia bayi 0-24 bulan, karena merupakan masa pertumbuhan dan perkembangan yang pesat, sehingga kerap diistilahkan sebagai periode emas sekaligus periode kritis. WHO dan UNICEF merekomendasikan empat hal penting, salah satunya adalah memberikan MP-ASI. Masalah penting dalam pemberian MP-ASI mencakup waktu pemberian MP-ASI, frekuensi, porsi, jenis makanan, dan cara pemberian MP-ASI pada tahap awal. Penelitian bertujuan untuk menganalisis hubungan tingkat pengetahuan dan sikap ibu tentang MP-ASI terhadap ketepatan pemberian MP-ASI bayi usia 6-12 bulan. Metode penelitian ini menggunakan desain penelitian Cross Sectional dengan jenis penelitian kuantitatif, disajikan dengan cara deskriptif analitik dengan jumlah responden sebanyak 60 orang. Data yang dikumpulkan dengan metode wawancara yaitu karakteristik ibu, pengetahuan ibu, sikap ibu, dan ketepatan pemberian MP-ASI, kemudian dianalisis dengan Chi-Square dengan CI 95%. Hasil penelitian menunjukkan bahwa ibu memiliki pengetahuan sedang mengenai MP-ASI sebanyak 80%, sikap negatif terhadap pemberian MP-ASI sebanyak 51,7%, dan tidak tepat dalam pemberian MP-ASI sebanyak 56,7%. Terdapat hubungan antara tingkat pengetahuan ibuÂ (p= 0,000) dan sikap ibu (p= 0,000) mengenai MP-ASI dengan ketepatan pemberian MP-ASI. Kesimpulan, tingkat pengetahuan dan sikap ibu tentang MP-ASI berkorelasi dengan ketepatan pemberian MP-ASI pada bayi usia 6-12 bulan di Kelurahan Lubang Buaya, Jakarta Timur.